Experimental tests for the assessment of residual strength of r.c. structures after fire – Case study. (1st February 2022) - Frappa, Giada; Pauletta, Margherita; Di Marco, Caterina; Russo, Gaetano
Highlights: Several test methods are used to assess the damages in a r.c. structure ham factory. The advantages and limitations of the adopted test methods are pointed out. In the wall and in the adjacent frame members very different damage is found. The amount of reinforcement strongly influences the deterioration of the concrete. Stirrups are added in columns and beams to confine concrete with inner delamination. Abstract: A fire in a ham factory in San Daniele del Friuli caused serious damage to the prefabricated reinforced concrete (r.c.) roof panels and smaller damages to beams, columns and walls. In this paper the data captured during preliminary inspection of the building structure are described. To determine the residual strength of steel reinforcements and concrete of r.c. structural elements, a test program with laboratory and in situ tests is presented. The program includes test methods that are able to catch the variability of concrete degradation with distance from the heated surface. Test results are presented and their acceptability in relation to Italian Code is discussed. It is found that the amount of transversal and longitudinal reinforcements strongly influences the deterioration of the concrete due to fire and, consequently, the strength of structural elements. On the basis of tests results, a discussion on the advantages and limitations of the adopted test methods useful for the designers is performed. To restore the load-bearing capacity of the structure, repairs of columns and beams in the first three bays of the central frame are proposed together with the substitution of the roof over the receiving area.